Assessing the Impacts of Land use/cover Change on the Hydrological Response of Temcha watershed, upper Blue Nile basin, Ethiopia - Dilnesa, Walelgn (International Journal of Scientific Research in Civil Engineering, 2018)
Information on the relationship between hydrologic response and land use /cover change was vital for the proper management of water resources and land use planning across the world.  The main objective of this study was to assess the impacts of land use/cover change on the hydrological response of Temcha watershed. ARC GIS did the hydrological modeling with an extension of ARC SWAT model and the model calibration and validation by SWAT CUP.  The result in the calibration and validation period showed a good agreement between the observed and simulated data, both in the calibration and validation period respectively.  the land use/ cover change had a significant impact on modeled watershed hydrologic response due to the transition from forest, grass, and shrub land to cultivated land areas resulted in annual and seasonal water yield, total aquifer recharge and surface runoff potential. These results demonstrate the usefulness of integrating remote sensing and distributed hydrologic models using GIS for assessing watershed conditions and the relative impacts of land cover transition on the hydrologic response continuous.
Keywords: ARC GIS; land use /cover; SWAT; Temcha Watershed